Analisis Struktur Pasar Industrial Pertelivisian Di Indonesia - A.G Sudibyo (Inter Komunika, 2016)
This research is aimed to analyze the television industrial media market structure in Indonesia. The perspective qualitative description `is used to collect data by applying the in-depth interview with some key figures in the television media industry, and relevant references. By using The Industrial Organizational Model Prespective in the economic media theoretical framework, this research is to analyze the aspect of market structure, regulations, economic and political system that influence the television media market in Indonesia. The result shows that the market is oligopoly high competition occurs with has caused the taken over and merger which followed by domination of ownerships in some of the industrial television media market structure. TVRI, state owned television, had dominated during the New Era.  Regulations have changed during the Reformation Era wherein the Government has given permission for private television companies to operate. RCTI was the first private television company, then followed by other television companies such as SCTV, Metro TV, TPI, ANTV, JakTV, Elshinta TV and MNC.